Cutting Edge: Immunological consequences and trafficking of human regulatory macrophages administered to renal transplant recipients. - Hutchinson, J; Riquelme, P; Sawitzki, B; Tomiuk, S; Miqueu, P; Zuhayra, M; Oberg, H; Pascher, A; Lützen, U; Janssen, U; Broichhausen, C; Renders, L; et al. (2011)
Regulatory macrophages (M regs) were administered to two living-donor renal transplant recipients. Both patients were minimized to low-dose tacrolimus monotherapy within 24 wk of transplantation and subsequently maintained excellent graft function. After central venous administration, most M regs remained viable and were seen to traffic from the pulmonary vasculature via the blood to liver, spleen, and bone marrow. By 1 y posttransplantation, both patients displayed patterns of peripheral blood gene expression converging upon the IOT-RISET signature. Furthermore, both patients maintained levels of peripheral blood FOXP3 and TOAG-1 mRNA expression within the range consistent with nonrejection. It is concluded that M regs warrant further study as a potential immune-conditioning therapy for use in solid-organ transplantation. The results of this work are being used to inform the design of The ONE Study, a multinational clinical trial of immunomodulatory cell therapy in renal transplantation.